2020
DOI: 10.1121/10.0000718
|View full text |Cite
|
Sign up to set email alerts
|

Task-evoked pupil response for accurately recognized accented speech

Abstract: Unfamiliar second-language (L2) accents present a common challenge to speech understanding. However, the extent to which accurately recognized unfamiliar L2-accented speech imposes a greater cognitive load than native speech remains unclear. The current study used pupillometry to assess cognitive load for native English listeners during the perception of intelligible Mandarin Chinese-accented English and American-accented English. Results showed greater pupil response (indicating greater cognitive load) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…Because of this, it may be difficult to differentiate between the effects of the masking of the speech and the effects of the induction of effort in response to the masking, since these two effects would be highly correlated. However, because participants in our study were able to perceive the speech at near 100% accuracy, the effects we saw on the pupillary response could not be explained directly by the masking of the speech but more likely by the increase in effort experienced by the listeners (see also Kuchinsky et al, 2013;McLaughlin & Van Engen, 2020). Therefore, our results provide strong evidence that the pupillary response is highly sensitive to changes in listening effort, not just changes in intelligibility.…”
Section: Acoustic Challenge and The Pupillometric Responsementioning
confidence: 52%
“…Because of this, it may be difficult to differentiate between the effects of the masking of the speech and the effects of the induction of effort in response to the masking, since these two effects would be highly correlated. However, because participants in our study were able to perceive the speech at near 100% accuracy, the effects we saw on the pupillary response could not be explained directly by the masking of the speech but more likely by the increase in effort experienced by the listeners (see also Kuchinsky et al, 2013;McLaughlin & Van Engen, 2020). Therefore, our results provide strong evidence that the pupillary response is highly sensitive to changes in listening effort, not just changes in intelligibility.…”
Section: Acoustic Challenge and The Pupillometric Responsementioning
confidence: 52%
“…Munro and Derwing (Munro & Derwing, 1995a) compared these three measures for 18 linguistically-aware subjects and found mixed results: for the majority of subjects, comprehensibility ratings (i.e., a scale from 1 = 'extremely easy to understand', to 9 = 'impossible to understand') positively predicted both accentedness ratings and intelligibility scores; however, accentedness ratings and intelligibility scores had no significant relationship for the majority of subjects, and a significant negative trend for five of them. Similarly, McLaughlin and Van Engen (2020) found that even completely intelligible non-native speech was rated by native listeners as sounding more accented than native speech. Thus, for the purposes of this review each of these measures will be defined as above, and it should be noted that correlations between each measure may not always be reliable.…”
Section: Listening To Non-native Speechmentioning
confidence: 87%
“…In particular, it is believed that a better understanding of mental effort allocation will allow a more comprehensive picture of hearing impairment (McGarrigle et al., 2014). Effortful listening is also a common experience for individuals listening to speech in a second (i.e., nonnative) language or in an unfamiliar accent (Borghini & Hazan, 2018; McLaughlin & Van Engen, 2020). Repeated or sustained episodes of effortful listening may lead to an exacerbated sense of tiredness or fatigue.…”
Section: Introductionmentioning
confidence: 99%